Which functional outcome measures can we use as a surrogate for exercise capacity during remote cardiopulmonary rehabilitation assessments? A rapid narrative review. Issue 4 (7th December 2020) - Houchen-Wolloff, Linzy; Daynes, Enya; Watt, Amye; Chaplin, Emma; Gardiner, Nikki; Singh, Sally
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has seen many cardiopulmonary rehabilitation services delivering programmes remotely. One area of concern is how to assess exercise capacity when a supervised exercise test is not possible. The aim of this review was to examine the relationship between functional exercise tests and recommended exercise tests for cardiopulmonary rehabilitation. Methods: A rapid narrative review was carried out. Searches were conducted by two of the study authors. The study had the following features. Participants: adults, all with long-term conditions; intervention: any/none; outcome: Duke activity status index (DASI), sit to stand (STS, 30 s, 1 min and 5 repetitions), short physical performance battery (SPPB), 4-metre gait speed (4MGS) or step test (Chester/others) AND directly compared to one of the recommended exercise tests for cardiopulmonary rehabilitation: 6-min walk test (6MWT), incremental shuttle walk test (ISWT) or cardiopulmonary exercise test (CPET) in terms of reporting agreement/correlation; Study design: primary research only, controlled trials or observational studies. Results: Sixteen articles out of 249 screened were included (n=2271 patients). Overall, there were weak–strong correlations for the included tests with a recommended exercise test (r=0.38–0.85). There were few reported issues with feasibility or safety of the tests. However, all tests were supervised in a clinical setting. The test that had the highest correlation with the field walking test was the 4MGS with the ISWT (r=0.78) and with the 6MWT (r=0.85). Discussion: The 4MGS has the highest correlation with routine measures of exercise tolerance. However, it may be difficult to standardise in a remote assessment or to prescribe exercise from. Clinicians should strive for face-to-face standardised exercise tests where possible to be able to guide exercise prescription. Clinicians should strive for face-to-face standardised exercise tests where possible to be able to guide exercise prescription https://bit.ly/34saiQR